Scientist in India - A Statistical Study - Planning Commission (Planning Commission, 1959)
The 1959 statistical study on scientists in India provides a comprehensive assessment of the size, composition, and characteristics of the country’s scientific workforce as of 1955. Drawing on data from the National Register of Scientific and Technical Personnel and earlier manpower studies, the report analyzes age distribution, educational qualifications, employment sectors, specialization, and salary patterns. It highlights rapid growth in scientific manpower, moderate register coverage, concentration of scientists in education and government, and notable disparities in specialization and income. The findings offer a critical empirical foundation for planning scientific education, employment, and policy to support India’s national development goals.
Planning Commission Perspective Planning Division
Planning Commission Perspective Planning Division
Keywords: Scientific Manpower In India; National Register Of Scientists; Planning Commission Studies; Employment Patterns; Educational Qualifications; Salary Structure; Research And Teaching Roles; Workforce Demographics; Specialization Trends; Human Resource Planning